Launching enterprise data backup and recovery solutions: the case of Ozonetel. (21st May 2010) - Kumar, Sujit; Varma, Siddharth
Ozonetel Systems Pvt. Ltd. is a company set up in 2008 by entrepreneur CSN Murthy, as a subsidiary of Rocsys Technology. Ozonetel systems have focused on the data, network and voice security offerings for enterprises. The advent of the internet has brought in several challenges in terms of security of data and network systems. While big companies can develop their own security products, or can buy them, small and medium companies have neither the financial muscle nor technological strength for doing this. Ozonetel wanted to target SMEs across various sectors. Ozonetel developed a solution with features like automatic storage from host computers, incremental backup, block level de-duplication, etc. However, the USP of the product was 'customised data backup and recovery solution at half the price of MNCs'. The company faced problems in reaching different market sectors despite being based in Hyderabad, a software hub. Determined to exploit its first mover advantage, Ozonetel decided to study the buying behaviour for IT usage across sectors and merge the results with an earlier study focusing on lack of market penetration of MNCs. With the help of a few marketing interns from the Indian Institutes of Management (IIMs), Ozonetel carried out this study in and around Hyderabad.